Enterprising psychometrics and poverty reduction - Klinger, Bailey (SpringerBriefs in Psychology, 2013)
As the deadline for the Millennium Development Goals draws near, one of the most critical--global poverty reduction--remains at best a work in progress. But as emerging markets beckon millions of aspiring business owners to set up shop, age-old barriers to funding prevent them from getting started. One answer lies in psychometrics, which  enables lenders to assess applicants' potential for success in developing their enterprises when traditional credit applications fall short.   Enterprising Psychometrics and Poverty Reduction sets out in accessible detail this innovative approach to risk evaluation, which uses methods similar to psychometric tools used in corporate hiring. The book evaluates this approach in six financial organizations in Kenya, Colombia, Peru, and South Africa, with extensive charts and tables breaking down each program's profitability and effectiveness. Especially by eliminating disparities that prevent women from accessing credit, this assistance fuels long-range economic growth and general well-being. This concise volume:  Explains the psychometric approach to credit and its methodologies. Identifies core characteristics shared by successful small business owners. Outlines a novel approach to credit scoring models for small businesses. Reviews the relevant literature on personality and personality testing. Features representative success stories. Discusses implications for implementing psychometric loan technologies in banks worldwide, and its potential relationship to training programs. Enterprising Psychometrics and Poverty Reduction offers message and methods to professionals and researchers in psychology, economics, development, and finance, especially those involved in global development, the psychology of poverty reduction, banking in emerging markets, and NGOs.